2018
DOI: 10.1021/acs.orglett.8b01484
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium-Catalyzed Dehydrogenation of N-Heterocycles in Water

Abstract: In this paper, the dehydrogenation of tetrahydroquinolines using oxovanadium(V) catalysts under mild conditions in water and oxygen atmosphere is described. This catalytic technology was successfully applied to a range of other structurally related N-heterocycles, and a reaction mechanism is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 46 publications
(21 reference statements)
1
21
0
Order By: Relevance
“…At this stage in the cycle, the addition of water to C might yield tetrahydroisoquinoline 4a, which was observed by proton nuclear magnetic resonance ( 1 H NMR) analysis (vide supra), and (S)-6b. Dehydrogenative aromatization of 4a proceeds via intermediate C and a single-electron transfer from the electron-rich nitrogen center to vanadium(V) forms the intermediate D, which undergoes the dehydrogenative aromatization to give the desired product 5a [35]; when (2,2,6,6-tetramethylpiperidin-1-yl)oxidanyl (TEMPO) (1.0 equivalent) was added to the optimal conditions, no desired product 5a was obtained at all. Under degassed N 2 instead of air, the sequential reaction proceeded to give 5a, probably due to easily auto-oxidation of 4a during analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage in the cycle, the addition of water to C might yield tetrahydroisoquinoline 4a, which was observed by proton nuclear magnetic resonance ( 1 H NMR) analysis (vide supra), and (S)-6b. Dehydrogenative aromatization of 4a proceeds via intermediate C and a single-electron transfer from the electron-rich nitrogen center to vanadium(V) forms the intermediate D, which undergoes the dehydrogenative aromatization to give the desired product 5a [35]; when (2,2,6,6-tetramethylpiperidin-1-yl)oxidanyl (TEMPO) (1.0 equivalent) was added to the optimal conditions, no desired product 5a was obtained at all. Under degassed N 2 instead of air, the sequential reaction proceeded to give 5a, probably due to easily auto-oxidation of 4a during analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Lewis acidic vanadium(V) complex 6 would promote a Pictet-Spengler reaction of imine intermediate 3 formed by the condensation of aniline 1 and benzaldehyde 2 to afford tetrahydroisoquinoline 4. A subsequent dehydrogenative aromatization of 4, assisted by the same vanadium(V) complex, now operating as a one-electron oxidant, would yield the desired phenanthridine product 5 [28,35].…”
Section: Introductionmentioning
confidence: 99%
“…The present sustainable and economical approach exhibits the advantages of high catalytic potential, operational without additives, and sufficiently stability and recyclability for up to ve reuses in comparison with reported protocols. [157][158][159] Balaraman et al reported a Co-phenanthroline complex adsorbed on GO (Co-Phen@C) as a NC in the acceptorless dehydrogenation of saturated aza-heterocycles to Nheteroaromatics for the synthesis of quinoline (35a), indoles (88d), isoquinolines (39b), quinoxalines (38d), and quinazolines (42e) using potassium tert-butoxide as the base (Scheme 76). 160 They synthesized the required catalyst via the sonochemical treatment of Co(II) acetylacetonate and 1,10-phenanthroline to obtain a Co-phenanthroline complex followed by its adsorption on exfoliated GO.…”
Section: Cunp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%
“…Chlorohydrins and ECH were used to prepare derivatives of pyridine [139][140][141], phtalazines [142][143][144], oxazolidinone [122,145,146], triazinones [147], thioglycoside [148] and aziridines [149]. N-Heterocycles have wide applicability as antibiotics [150][151][152]. The evaluation of novel agents for antimicrobial activity is a very important field of study due to the emergence of bacterial resistance to classical antibiotics.…”
Section: Funcionalization Of Aza-heterocyclic Compoundsmentioning
confidence: 99%